2014
DOI: 10.1111/spol.12079
|View full text |Cite
|
Sign up to set email alerts
|

School Choice in London and Paris – A Comparison of Middle‐class Strategies

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 43 publications
3
31
0
6
Order By: Relevance
“…Some evidence has suggested that parents from higher socioeconomic (SES) backgrounds are more likely to value academic performance than those from lower SES backgrounds (Hastings, Van Weelden, and Weinstein 2007;Leroux 2015) providing motivation to gain entry to selective schools. A body of research has also indicated the role of peer group and social mix in influencing the schools that parents consider and choose (Bagley, Woods, and Glatter 2001;Benson, Bridge, and Wilson 2015;Burgess et al 2011). In line with earlier work (Francis and Archer 2005;Modood 2003), Cribb, Sibieta, and Vignoles (2013, 8) suggest that "differences in educational attitudes and aspirations" may play a role in where children attend school and their attainment.…”
Section: Why Are Fewer Disadvantaged Pupils Attending Grammar Schools?mentioning
confidence: 72%
“…Some evidence has suggested that parents from higher socioeconomic (SES) backgrounds are more likely to value academic performance than those from lower SES backgrounds (Hastings, Van Weelden, and Weinstein 2007;Leroux 2015) providing motivation to gain entry to selective schools. A body of research has also indicated the role of peer group and social mix in influencing the schools that parents consider and choose (Bagley, Woods, and Glatter 2001;Benson, Bridge, and Wilson 2015;Burgess et al 2011). In line with earlier work (Francis and Archer 2005;Modood 2003), Cribb, Sibieta, and Vignoles (2013, 8) suggest that "differences in educational attitudes and aspirations" may play a role in where children attend school and their attainment.…”
Section: Why Are Fewer Disadvantaged Pupils Attending Grammar Schools?mentioning
confidence: 72%
“…Some proponents of school choice argue that expanding non-neighbourhood options can 'liberate' lower-SES and nonwhite students from traditional public schools in lower-resourced neighbourhoods. Critics, however, worry that the increasing provision of school choice provides white and higher-SES parents greater opportunities to bypass schools with a higher proportion of minority or low-income students, thus upholding school segregation, as recent work in the US (Renzulli and Evans, 2005;Saporito, 2003;Saporito and Sohoni, 2006), UK (Benson et al, 2015;Hamnett et al, 2013) and Europe (Noreisch, 2007;Oberti, 2007) suggests. As whites opt out of neighbourhood public schools with a higher presence of nonwhite and poor students, the racial compositional match between neighbourhoods and schools loosens -schools become less white than their surrounding neighbourhood.…”
mentioning
confidence: 99%
“…One possible reason for the inconsistency of these results is that schools do not always react as expected to parents’ school choices, because parents do not send clear signals when choosing one school over another (Manna ; Van Dunk and Dickman ). Another possibility is that parents’ perception of school quality is linked more strongly to schools’ composition and reputation than to schools’ performance, while the connection between schools’ composition and reputation on the one hand and schools’ performance on the other hand may be weak (Benson et al ). Hence, it is possible that the availability of an exit option incentivizes schools to influence school composition and reputation rather than test results.…”
Section: The Three Presuppositionsmentioning
confidence: 99%